The role of ventilatory support for long‐term outcomes after critical infection with COVID‐19: A prospective cohort study. (27th October 2021) - Hanna, Gabriel; Bankler, Sara; Schandl, Anna; Roël, Mari; Hedman, Anders; Andersson Franko, Mikael; Lyngå, Patrik; Geborek, Anne; Joelsson‐Alm, Eva; Söderberg, Mårten; Darlington, Pernilla
Abstract: Objectives: The full range of long‐term health consequences in intensive care unit (ICU) survivors with COVID‐19 is unclear. This study aims to investigate the role of ventilatory support for long‐term pulmonary impairment in critically ill patients and further to identify risk factors for prolonged radiological recovery. Methods: A prospective observational study from a single general hospital, including all with COVID‐19 admitted to ICU between March and August 2020, investigating the association between ventilatory support and the extent of residual parenchymal changes on chest computed tomography (CT) scan and measurement of lung volumes at follow‐up comparing high‐flow nasal oxygen (HFNO) or non‐invasive ventilation (NIV) with invasive ventilation. A semi‐quantitative score (CT involvement score) based on lobar involvement and a total score for all five lobes was used to estimate residual parenchymal changes. The association was calculated with logistic regression and adjusted for age, sex, smoking, and severity of illness. Results: Among the 187 eligible, 86 had a chest CT scan and 76 a pulmonary function test at the follow‐up with a median time of 6 months after ICU discharge. Residual lung changes were seen in 74%. The extent of pulmonary changes was similar regardless of ventilatory support, but patients with invasive ventilation had a lower total lung capacity 84% versus 92% of predicted ( p < 0.001). Conclusions: The majority of ICU‐treated patients with COVID‐19 had residual lung changes at 6 months of follow‐up regardless of ventilator support or not, but the total lung capacity was lower in those treated with invasive ventilation.